Analysis of Business Credit Policy for The Poor in Gianyar Regency - I Putu Dharmanu Yudartha; Komang Adi Sastra Wijaya (Westscience Press, 2024)
Poverty is a major issue faced by many local governments, including Gianyar District. To empower people experiencing poverty, the Gianyar district government has implemented multiple policies, especially after the COVID-19 pandemic. These policies provide business loans for those affected by poverty, aiming to help them get back on their feet. This study focuses on analyzing the business credit policies for people experiencing poverty in Gianyar Regency, using qualitative methods of a descriptive approach. One of the significant findings of this study is that the current policy alternative (status quo) is still relevant for the distribution of people's business credit. This is because its technical feasibility criteria meets the desired outcomes as stated in the regional regulations. However, the policy may not be effective in the long run as it depends on provincial revenues. Therefore, it is recommended to have policy synergy with national banks and Village-Owned Enterprises to provide credit to people experiencing poverty with low interest.